THE RESPONSIBILITIES OF THE NOTARY THIRD PARTY SERVICES (REALTOR) TO GET CLIENTS - Gafur, Abdul; Pramono, Budi; Sunardi, Sunardi (International Significance of Notary, 2022)
Notary is a profession with a very noble position (nobile officium). because of why a notary is burdened with obligations and prohibitions to obey. sometimes notaries are often negligent in their actions, this is triggered, by the increasing number of new notary graduates, giving rise to unhealthy competition however. This competition sometimes takes the form of ethical violations committed by a notary, such as using the services of other parties (brokers) to get clients. so this needs to be examined further regarding "the responsibility of a notary who uses the services of a third party (broker) to get a client" The rules or norms in positive law. The problem approach uses statutory approaches and approaches, with legal materials consisting of primary, secondary and non-legal materials. In the responsibility of a notary who uses the services of a broker to get a client, it is of course against the principle of decency contained in the laws and regulations for the position of a notary and is not justified and not allowed in the provisions of the notary's code of ethics, there are at least three aspects that can be accounted for by a notary. Moral responsibility, professional technical responsibility,legal responsibility. then in legal consequences for notaries who use brokerage services in finding clients can be charged with imposing sanctions by the honorary council as stated in article 6 of the notary's code of ethics, these sanctions are in the form of, reprimand, warning, scoring (temporary dismissal) from the association association, Onzetting (dismissal) from to members of the association, dishonorable discharge from the association.Keywords: Notary Responsibilities, Using Broker Services, Clients